2019
DOI: 10.3390/jpm9020021
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptomic Toolbox: Resources for Interpreting Large Gene Expression Data within a Precision Medicine Context for Metabolic Disease Atherosclerosis

Abstract: As one of the most widespread metabolic diseases, atherosclerosis affects nearly everyone as they age; arteries gradually narrow from plaque accumulation over time reducing oxygenated blood flow to central and periphery causing heart disease, stroke, kidney problems, and even pulmonary disease. Personalized medicine promises to bring treatments based on individual genome sequencing that precisely target the molecular pathways underlying atherosclerosis and its symptoms, but to date only a few genotypes have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…Atherosclerosis is associated with metabolic diseases. 142 Gut mycobiota dysbiosis has also been shown to be related with the development of carotid atherosclerosis. 132 In a study of 33 subjects who had fecal samples collected for ITS amplicon sequencing, the subjects were divided into two groups of 12 nonobese subjects versus 21 obese subjects.…”
Section: Gut Mycobiome In Metabolic Diseasesmentioning
confidence: 99%
“…Atherosclerosis is associated with metabolic diseases. 142 Gut mycobiota dysbiosis has also been shown to be related with the development of carotid atherosclerosis. 132 In a study of 33 subjects who had fecal samples collected for ITS amplicon sequencing, the subjects were divided into two groups of 12 nonobese subjects versus 21 obese subjects.…”
Section: Gut Mycobiome In Metabolic Diseasesmentioning
confidence: 99%
“…Despite these disadvantages and when analytical and preanalytical conditions were optimized, many studies have reported a high correlation of gene expression between FFPE and FF samples, 54,57,59,[72][73][74][75][76][77][78][79][80][81][82] although the RNA extracted from the FFPE samples was most often degraded and continued to degrade with age. Some studies have also investigated different extraction techniques or sequencing methods to optimize the workflow for archival materials.…”
Section: The Caveats Of Ffpementioning
confidence: 99%
“…Into the future, the diagnosis of atherosclerosis will move beyond simple anatomical information to more qualitative characterisation. This will likely consist of complex panels including circulating protein biomarkers, cellular transcriptome analysis34 and extracellular vesicle examination in combination with molecular non-invasive and invasive imaging tools. The ultimate aims of this approach would be in the first instance to identifying patients at high risk (‘upstream’ of an event) by identifying the presence and activity of specific pathogenic biological processes that may benefit from specific targeted intervention; and second, to provide specific patient-level insights into prognosis (‘downstream’ of the event) and duration and response of directed therapy.…”
Section: Concepts Of ‘Inflammation’ and The Use Of Biomarkersmentioning
confidence: 99%